BENTUK PENYAJIAN TARI JEPIN TEMBUNG PANJANG DI KOTA PONTIANAK - Firsti Irda Kurnia Asih; Ismunandar Ismunandar; Regaria Tindarika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract The present research was conducted in order to describe the data and the information completely about the Jepin Tembung Panjang dance. The purpose of this research is to describe and record the Jepin Tembung Panjang dance in written form, pictures, and video. The method that used in this research is descriptive analysis in form of descriptive qualitative research and use the ethnochoreology approach with choreography discipline. The sources of this research are Muhammad Yusuf Dahyani and Anwar Dja’far that knowing about the form of presenting the Jepin Tembung Panjang in Pontianak city, Kalimantan Barat. The data collection of this research are observation, interview and documentation study. Technique of testing the validity data that used are extension of observations and triangulation technique. Jeping Tembung Panjang dance can be danced en masse with a multiple of four dancers. The instruments to company this are Beruas, Gambus, Akordion dan Biola. The Jeping Tembung Panjang dance will use realist makeup. This dance will be danced by two dancer those are male and female. Keywords: form of presentation, Jepin Tembung Panjang dance.